2018
DOI: 10.5194/gmd-11-61-2018
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of microtopographic snow redistribution and lateral subsurface processes on hydrologic and thermal states in an Arctic polygonal ground ecosystem: a case study using ELM-3D v1.0

Abstract: Abstract. Microtopographic features, such as polygonal ground, are characteristic sources of landscape heterogeneity in the Alaskan Arctic coastal plain. Here, we analyze the effects of snow redistribution (SR) and lateral subsurface processes on hydrologic and thermal states at a polygonal tundra site near Barrow, Alaska. We extended the land model integrated in the E3SM to redistribute incoming snow by accounting for microtopography and incorporated subsurface lateral transport of water and energy (ELM-3D v1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 98 publications
1
25
1
Order By: Relevance
“…The variations in our estimates for seven landscape types were potentially biased because they ignored the lateral surface hydrologic and thermal processes. The spatial variability in soil moisture and soil temperature can be overpredicted if the lateral subsurface hydrologic and thermal processes are excluded (Bisht et al, ), and the same is true for the spatial variability in CH 4 emissions in Arctic polygonal landscapes. By incorporating these surface processes, the CH 4 models can improve the representation of lateral hydrologic and thermal transport, and thereby improve the accuracy of estimations (Aas et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The variations in our estimates for seven landscape types were potentially biased because they ignored the lateral surface hydrologic and thermal processes. The spatial variability in soil moisture and soil temperature can be overpredicted if the lateral subsurface hydrologic and thermal processes are excluded (Bisht et al, ), and the same is true for the spatial variability in CH 4 emissions in Arctic polygonal landscapes. By incorporating these surface processes, the CH 4 models can improve the representation of lateral hydrologic and thermal transport, and thereby improve the accuracy of estimations (Aas et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…1a and c). The polygonal tundra on Samoylov Island has been previously investigated in a number of studies, with a particular focus on measuring its water and energy balances (Boike et al, 2008;Langer et al, 2011a, b;Helbig et al, 2013). Moisture levels on the island are spatially variable with a high abundance of polygonal ponds and a few larger water bodies in its central part and dryer, welldrained areas towards the margins of the island (Muster et al, 2012).…”
Section: Study Areamentioning
confidence: 99%
“…We used an instantaneous infiltration scheme which assumes rapid vertical water flow compared to the rates of other processes represented in the model. This is a valid assumption for the upper soil layers of tundra wetlands, which are typically characterized by large hydraulic conductivities (Boike et al, 2008) and in which infiltration into the active layer is mainly controlled by thaw depth (Zhang et al, 2010).…”
Section: Hydrology Scheme For Unfrozen Groundmentioning
confidence: 99%
“…A major weakness of current generation LSMs is the numerical techniques used to obtain solution of the linear and nonlinear system of equations (SoE) that result from spatial and temporal discretization of one‐dimensional biophysical processes (Clark & Kavetski, ). For example, the numerical algorithm that solves for canopy and soil skin temperatures in the nonlinear canopy radiative model of the Community Land Model (CLM; Oleson et al, ) and the E3SM Land Model (ELM; Bisht et al, ; Riley et al, ; Tang & Riley, ) accepts the last solution iteration when maximum allowable iteration count is reached even though the change in iterate value remains larger than the tolerance value (Oleson et al, ). Analysis by Kavetski and Clark () using eight time stepping schemes for six hydrologic models in 13 basins showed that unreliable time stepping schemes, irrespective of model structure, lead to serious numerical artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, current generation LSMs have been desgined to only simulate one‐dimensional processes while several recent studies have demonstrated the need to explicitly account for lateral subsurface processes. Bisht et al () showed that inability of ELM to include lateral redistribution of water and energy in the subsurface leads to an overestimation of spatial variability of soil moisture and soil temperature in Arctic polygonal ground ecosystem. Chang et al () demonstrated that incorporation of lateral water flow and water vapor diffusion within the soils in a watershed scale model leads to an improved prediction of the transpiration to evapotranspiration ratio.…”
Section: Introductionmentioning
confidence: 99%